Emergency Department Adolescent Suicidality: A Pilot Study to Determine How Common Actual Attempts Are. Issue 2 (February 2022) - Sheridan, David C.; Lin, Amber
Abstract : Objective: Adolescent mental health is a rapidly escalating presentation to emergency departments in the United States with depression and suicidal thoughts being the most prevalent condition. Much of the research and focus has been on preventing future attempts. However, one outcome that may be very important in addition to focus on is the impact of presentations for thoughts without self-injury. The aim was to evaluate outcomes of interest for a larger prospective observational adolescent suicidal trial including frequency of suicide attempts versus thoughts and factors associated with each outcome. Methods: This is a prospective pilot study of adolescents at a single pediatric emergency department between December 2016 and September 2017 with acute suicidality. We used descriptive statistics to compare chief complaint, medical history, Patient Health Questionnaire-9 (PHQ-9), and outcomes including final disposition and total emergency department length of stay (LOS). We used t tests for continuous outcomes, χ 2 test for categorical data, and Fisher exact tests for categorical and sparse data (20% of cell sizes of <5). Results: Forty-one patients were enrolled, with 43.9% having an attempt; 72.2% of attempts were the result of an ingestion, and approximately 54% were over-the-counter medications. The average (SD) LOS was 30.8 (31.2) hours, and 63% were discharged home to outpatient services. There were no significant differences in age, chief complaint (except overdose), medical history, final disposition, total LOS in the ED, and the PHQ-9. Scores of the PHQ-9 were, on average (SD), 18.51 (4.7) across the entire cohort, 18.06 (5.75) in patients with an attempt, and 18.87 (3.77) in patients without an attempt ( P = 0.59). Conclusions: Adolescent mental health is a growing issue for pediatric emergency departments nationally. Prospective research to identify factors associated with worsening outcomes is important to identify and potentially modify if possible. This study did not find any specific factors associated with a suicide attempt, but found that less than half of patients presenting with suicidality actual made an attempt. Future research should focus on not only limiting suicide attempts but also using decreased emergency department visits for worsening thoughts as an outcome of interest.